2020
DOI: 10.1111/1541-4337.12558
|View full text |Cite
|
Sign up to set email alerts
|

Destructuring and restructuring of foods during gastric digestion

Abstract: All foods harbor unique length scale‐dependent structural features that can influence the release, transport, and utilization of macro‐ or micronutrients in the human gastrointestinal tract. In this regard, food destructuring and restructuring processes during gastric passage significantly influence downstream nutrient assimilation and feelings of satiety. This review begins with a synopsis of the effects of oral processing on food structure. Then, stomach‐centric factors that contribute to the efficacy of gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 179 publications
0
26
0
Order By: Relevance
“…4a). It can be hypothesized that the presence of milk proteins, undergoing unfolding, crosslinking and aggregation during the gastric phase, 53 could further protect the bacteria.…”
Section: Food and Function Papermentioning
confidence: 99%
“…4a). It can be hypothesized that the presence of milk proteins, undergoing unfolding, crosslinking and aggregation during the gastric phase, 53 could further protect the bacteria.…”
Section: Food and Function Papermentioning
confidence: 99%
“…In the context of starch digestion, this implies that the extent of physical breakdown of solid or semisolid starch‐based foods prior to small intestinal digestion is crucial for the subsequent glucose absorption process. Although the physical breakdown processes of food structure in the mouth and stomach have been previously reviewed (Acevedo‐Fani & Singh, 2021; Brownlee et al., 2018; Capuano & Pellegrini, 2019; Golding, 2019; Guo et al., 2020; Singh et al., 2015; Somaratne et al., 2020), how these breakdown processes impact small intestinal digestion and glycemic response of starch‐based foods has not been discussed…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of expectorated bolus samples revealed that the indigenous matrix of the almond cell wall is largely maintained throughout the journey from the oral cavity through the alimentary canal, such that only a low proportion of almond lipids is bio-accessible during digestion. This natural encapsulation of lipids has been proposed as an approach that could potentially enable the structuring of food components within a natural matrix to reduce energy availability and attenuate post-prandial lipid responses [ 79 , 80 ]. Food processes such as milling, pureeing, extrusion, refining, spray-drying, homogenization, mixing, crushing, roasting, baking, frying, and blanching can decrease the structural integrity of food matrices [ 10 ••] and increase the availability of macromolecule components such as fatty acids, amino acids, mono-, and di-saccharides [ 11 ].…”
Section: Impact Of Food Matrix On Energy Intake Satiety and Metabolic...mentioning
confidence: 99%